Bio‐Inspired Chemical Fabrication of Stretchable Transparent Electrodes. Issue 28 (18th March 2015) - Yu, You; Zhang, Yaokang; Li, Kan; Yan, Casey; Zheng, Zijian
<x xml:space="preserve">Abstract</x> Stretchable and transparent electrodes are fabricated by chemical deposition of metal thin films on natural veins of leaves at ambient conditions. These vein‐based transparent electrodes show excellent electro‐optical property (0.9 Ω sq−1 at 83% T) even at 50% tensile strains, ideal for flexible and stretchable optoelectronic devices.